2019
DOI: 10.1039/c8fo02298d
|View full text |Cite
|
Sign up to set email alerts
|

Protection of hepatocyte mitochondrial function by blueberry juice and probiotics via SIRT1 regulation in non-alcoholic fatty liver disease

Abstract: Blueberry juice and probiotics improves mitochondrial dysfunction and oxidative stress induced by nonalcoholic fatty liver disease (NAFLD), by modulating the SIRT1 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
(34 reference statements)
2
16
0
Order By: Relevance
“…Moreover, Sirt1 knockdown by siRNAs markedly abrogated the inhibitory effect of PSPC on PA-induced apoptosis in L02 cells. Consistent with these studies (12,23,35), our results revealed that PSPC might exhibit inhibitory effects on HFD-induced hepatic apoptosis via restoring Sirt1 level.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, Sirt1 knockdown by siRNAs markedly abrogated the inhibitory effect of PSPC on PA-induced apoptosis in L02 cells. Consistent with these studies (12,23,35), our results revealed that PSPC might exhibit inhibitory effects on HFD-induced hepatic apoptosis via restoring Sirt1 level.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, HFD remarkably reduced the protein expression of SirT1 as well as its activity in mouse livers, indicating that HFD-induced hepatic apoptosis may be associated with the down-regulation of Sirt1. It has been widely reported that some naturally occurring polyphenols, such as resveratrol, are Sirt1 activators, which exhibit beneficial effects on a variety of diseases including NAFLD (12,35). Our previous study also demonstrated that troxerutin, a flavonoid, markedly renewed Sirt1 levels to protect mouse liver from HFD-induced steatosis (23).…”
Section: Discussionmentioning
confidence: 86%
“…Administration of mitoquinone mesylate (MitoQ), a mitochondrial-targeted antioxidant with high bioavailability, restores hepatic mitochondrial functions and ameliorates glucose intolerance and hepatic steatosis [61][62][63]. Antioxidant foods including blueberry juice and probiotics significantly reduce NAFLD-induced mitochondrial swelling and hepatic necrosis by restoring the mitochondrial respiratory chain function and suppressing the production of ROS [64]. Pretreatment with methionine alleviates the pathological changes associated with NAFLD by increasing GSH levels [60].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…[50][51][52] Several studies have demonstrated that SIRT1 reduces oxidative stress and the activation of SIRT1 by polyphenols would be beneficial in therapeutic intervention of a diversity of chronic diseases including hepatic steatosis. [6,[53][54][55] In this study, we observed that SIRT1 expression was reduced in the HF group. The present study was the first to demonstrate that ASE polyphenols and rosuvastatin significantly increased the SIRT1 expression, contributing to the reduction of oxidative stress in the liver and resolution of hepatic steatosis in obese mice.…”
Section: Discussionmentioning
confidence: 92%